Analisis Tingkat Digital Presence, Brand Awareness, dan Brand Interest PT Trijaya Pratama Futures (TPFx) pada Masyarakat Pengguna Media Digital - Steven Riski Tamba; Lina Fatimah Lishobrina (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Digital technology has transformed the way people obtain information, become familiar with brands, and choose products or services, including in the futures brokerage industry. This trend has prompted businesses to strengthen their digital presence as a means of increasing brand awareness and fostering brand interest among digital media users. The objective of this study is to evaluate the level of digital engagement, brand awareness, and brand interest in PT Trijaya Pratama Futures (TPFx) among the population of digital media users. This study employs a quantitative approach combined with a descriptive approach. Data were collected through purposive sampling by distributing an online questionnaire to 122 selected participants. The data were then analyzed using descriptive statistics to illustrate the characteristics of each research variable. Mean values, frequencies, and percentages were calculated. The results show that, in the moderate category, Digital Presence scored an average of 3.24, Brand Awareness scored an average of 3.10, and Brand Interest scored an average of 3.67. The findings indicate that the public is highly interested in learning about the services offered by PT Trijaya Pratama Futures, even though brand awareness remains relatively low.Therefore, businesses must optimize their digital marketing strategies by increasing their social media activity, optimizing their websites, providing educational content, and continuing to use various digital platforms to boost visibility, increase brand awareness, and expand their market reach.